2011
DOI: 10.1302/0301-620x.93b1.24987
|View full text |Cite
|
Sign up to set email alerts
|

Return to theatre following total hip and knee replacement, before and after the introduction of rivaroxaban

Abstract: Rivaroxaban has been recommended for routine use as a thromboprophylactic agent in patients undergoing lower-limb arthroplasty. However, trials supporting its use have not fully evaluated the risks of wound complications. This study of 1048 total hip/knee replacements records the rates of return to theatre and infection before and after the change from a low molecular weight heparin (tinzaparin) to rivaroxaban as the agent of chemical thromboprophylaxis in patients undergoing lower-limb arthroplasty. During a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 28 publications
4
70
1
1
Order By: Relevance
“…A pooled analysis of the 4 trials, however, indicated a very small increase in bleeding, 26 an issue of particular concern to some orthopedic surgeons who will also be reticent in initiating immediate-acting anticoagulants until 12 to 24 hours postoperatively. 27 Rivaroxaban nonetheless is a convenient and highly effective agent for the prevention of venous thrombosis after total hip or knee replacement (see Table 3 for dose/schedule) and is a good alternative to anticoagulants that require subcutaneous injections (eg, LMWHs, fondaparinux) or regular laboratory monitoring (eg, warfarin).…”
Section: Rivaroxaban In the Prevention And Treatment Of Vtementioning
confidence: 99%
“…A pooled analysis of the 4 trials, however, indicated a very small increase in bleeding, 26 an issue of particular concern to some orthopedic surgeons who will also be reticent in initiating immediate-acting anticoagulants until 12 to 24 hours postoperatively. 27 Rivaroxaban nonetheless is a convenient and highly effective agent for the prevention of venous thrombosis after total hip or knee replacement (see Table 3 for dose/schedule) and is a good alternative to anticoagulants that require subcutaneous injections (eg, LMWHs, fondaparinux) or regular laboratory monitoring (eg, warfarin).…”
Section: Rivaroxaban In the Prevention And Treatment Of Vtementioning
confidence: 99%
“…No difference in major bleeding events between both group (0.7 % vs 0.3 %; P=0.109). In the latest retrospective review, Jensen et al [42] associated rivaroxaban with more reoperations than LMWH after TKA (3.94 % vs 1.8 %; P= 0.046).…”
Section: Rivaroxabanmentioning
confidence: 99%
“…Wound complications including excessive wound hematoma, surgical site bleeding, and postsurgical wound infection were similar between rivaroxaban and enoxaparin in a pooled analysis of RECORD 1 and 2 [65] . However, the potential for an increased risk of wound complications associated with rivaroxaban has been brought into question by several recent institutional studies [66][67][68][69][70] . In a multicenter analysis of 13123 major orthopedic surgery patients (including 5974 THA), Jameson et al [69] found an increased rate of wound complications including hematoma, superficial wound infection, and deep infection requiring return to surgery, with rivaroxaban compared to enoxaparin use (3.85% vs 2.81%, P = 0.005).…”
Section: Post-surgical Vte After Elective Major Orthopedic Surgery Ofmentioning
confidence: 99%